GAMBARAN KARAKTERISTIK IBU HAMIL YANG MENGALAMI EKLAMPSIA - Trisetyaningsih, Yanita; Smaradika, Annisa (MEDIA ILMU KESEHATAN, 2018)
Background : Preeclampsia is the escalting blood preasure as high as 140/90 mmHg at the minimal level, proteinuria, and oedema of pregnant mothers. Preeclampsia is a risk that may be harmful for mother and fetus. Up to date, the cause of preeclampsia remains unrevealed, but preeclampsia can effect certain grups like mother with predisposing factors such as age, education, job, parity, history of preeclampsia, history of hypertesion, nurtritional status , etc. Objective : to identify The Description of Characteristics of Pregnant Mothers with Pre Eclampsia in PKU Muhammadiyah Hospital of Bantul during 1st January 2015 - 29th June 2017. Method : This was a descriptive and quantitative study with total sampling data collecting method which was aimed to present a description about age, parity, job, education, history of hypertension, history of preeclampsia, and nutritional status with preeclampsia affection. Result : Since the beginning of 2015 until mid 2017, there had been 49 preeclampsia cases, mostly in the group of age 20-35 years old (69,4%), multigravid pregnant mothers (77,6%), last education of Senior High School (49,0%), IMT aspect with more nutrition (71,4%), had no history of preeclampsia (63,3%), had history of hypertension (59,2%), other jobs or house-wives (40,8%). Conclusions : It is expected that the hospital should always pay attention to pregnant women who are at risk of preeclampsia, in order to reduce the incidence of preeclampsia occurring in the area of the hospital and can cope with the incidence of preeclampsia earlier. Keywords : Preeclampsia, Pregnant Women